2019
DOI: 10.3390/ijerph16091656
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Exposure to ETS (Environmental Tobacco Smoke), Urinary Cotinine, and Oxidative Stress Parameters in Pregnant Women—The Pilot Study

Abstract: Background: Exposure to ETS (environmental tobacco smoke) is one of the most toxic environmental exposures. Objective: To investigate the association of ETS with physiological, biochemical, and psychological indicators, as well as with urine antioxidant capacity (AC) and oxidative damage to lipids in a pilot sample of healthy pregnant women. Methods: Exposure to ETS was investigated via a validated questionnaire, and urine cotinine and the marker of oxidative damage to lipids via 8-isoprostane concentrations u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In adult smokers, an increase in DNA oxidation (Mesaros, Arora, Wholer, Vachani, & Blair, 2012), lipid peroxidation, and alteration in catalase, SOD, GPx activity and glutathione level (Arja et al, 2013;Li et al, 2007;Miri, Saadati, Ardi, & Firuzi, 2012;Ozbay & Dulger, 2002) were observed in different body fluids when compared with nonsmokers. Exposure of pregnant women to active or passive Cg smoking induced oxidative stress in the placenta (Argalasova et al, 2019;Sbrana et al, 2011). In addition, lower concentrations of catalase and total antioxidative capacity were reported in the umbilical cord blood of smokers than nonsmokers (Aycicek & Ipek, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…In adult smokers, an increase in DNA oxidation (Mesaros, Arora, Wholer, Vachani, & Blair, 2012), lipid peroxidation, and alteration in catalase, SOD, GPx activity and glutathione level (Arja et al, 2013;Li et al, 2007;Miri, Saadati, Ardi, & Firuzi, 2012;Ozbay & Dulger, 2002) were observed in different body fluids when compared with nonsmokers. Exposure of pregnant women to active or passive Cg smoking induced oxidative stress in the placenta (Argalasova et al, 2019;Sbrana et al, 2011). In addition, lower concentrations of catalase and total antioxidative capacity were reported in the umbilical cord blood of smokers than nonsmokers (Aycicek & Ipek, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…There are several limitations to this study. First, even though we controlled for several factors, including obesity [63], mental health [64], passive smoking [65], iodine deficiency [66], and exercise habits [67], other factors may also affect oxidative stress and should be investigated. Second, even though we measured stress markers at two points, we did not assess long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the undecided conclusions: first, low socioeconomic status followed by low birth weight and less breast milk in smoking mothers can be confounded with childhood obesity; second, there are no standardized methods for quantifying smoking doses, and the difficulty in estimating concentrations of smoking substances by questionnaires limits the interpretations of tobacco substances. Measuring the urinary concentration of cotinine, a nicotine metabolite, is useful for estimating accurate tobacco intake ( 6 , 7 , 14 ). Therefore, the relationship between tobacco substances and BMI trajectory in childhood can be interpreted more precisely by minimizing the above confounding factors.…”
Section: Introductionmentioning
confidence: 99%